(2x)-(3)=6

Simple and best practice solution for (2x)-(3)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x)-(3)=6 equation:


Simplifying
(2x) + -1(3) = 6

Multiply -1 * 3
(2x) + -3 = 6

Reorder the terms:
-3 + (2x) = 6

Solving
-3 + (2x) = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + (2x) = 6 + 3

Combine like terms: -3 + 3 = 0
0 + (2x) = 6 + 3
(2x) = 6 + 3

Combine like terms: 6 + 3 = 9
(2x) = 9

Divide each side by '2'.
x = 4.5

Simplifying
x = 4.5

See similar equations:

| 8r-29=-29 | | 7x-14(x+1)=-7x+24 | | 2+24=4 | | 6a+3-5=7a-23 | | 7x+(15y+3)=180 | | 12q-19=-4 | | f(x)=2x^2-3x+4 | | K/4=33/20 | | 9+10p=49 | | -3(-5v+6)-3v=2(v-4)-2 | | -4(3x+1)=-136 | | 4/x=1/5 | | 0.62-0.15x=0.25-0.1 | | f(x)=2x-3x+4 | | -7x+3=-11 | | -15-5t=15 | | 5x-4(-3/2x+2)=y | | 5x-5=12-68 | | f(x)=2x(4)-3x+4 | | 4x+13=8x+25 | | -x+42=4x | | -2.5+g=-1.3-1.1 | | (3x+4)(5x+9)= | | 36=8-7y | | 0.5x+1.2=0.8x-1.2 | | .75x=36.75 | | 9x+14=5x+2 | | x/3+x/6=5 | | g=7*1/2 | | 13(x+6)-3=3+-5 | | -0.10(33)+0.85x=0.05(x-2) | | f--40=-12 |

Equations solver categories